Impact of door-to-deployment time of venoarterial extracorporeal membrane oxygenation for out-of-hospital refractory cardiac arrest patients secondary to cardiovascular causes. (25th November 2020) - Muranishi, H; Zushi, R; Yagi, Y; Kawasaki, S; Tanaka, S; Fukuda, M; Kobata, H
Abstract: Background: Door-to-balloon time in patients with ST-elevation myocardial infarction is reported to be an independent predictor of the prognostic implication. However, the effect of door-to-deployment time (DTDT) of venoarterial extracorporeal membrane oxygenation (VA-ECMO) on patients with out-of-hospital cardiac arrest (OHCA) is unclear. Purpose: This single-center, retrospective, observational study aimed to evaluate the effect of DTDT of VA-ECMO for mortality or neurological outcome of extracorporeal cardiopulmonary resuscitation (ECPR) in patients with cardiogenic OHCA. Method: This single-center, retrospective, observational study was conducted from January 2008 to April 2019. The primary endpoint was 1-month overall survival measured after ECMO initiation. Moreover, the secondary endpoint was 1-month survival with favorable neurological functions defined as having a cerebral performance category score of 1 or 2. Result: A total of 3082 patients with OHCA were brought to our institution and 84 received ECPR. Of these, 51 consecutive adult patients with cardiogenic OHCA without sustained return of spontaneous circulation during transport were included in this analysis. Approximately 18 patients (18/51, 35.3%) survived after 1 month and were discharged. Among the survivors, 15 (15/18, 83.3%) were discharged with a favorable neurological outcome. The baseline characteristics between the survivors and non-survivors were not significantly different, except for the initial shockable rhythm [18/18 (100%) versus 28/33 (84.9%), P=0.03]. There were no significant differences between the median time from collapse to hospital arrival [31.0 min (IQR 25.0–31.0) versus 29.0 min (IQR 25.0–39.5), P=0.53] and from call to hospital arrival [28.0 min (IQR 22.0–32.5) versus 27.0 min (IQR 23.3–34.5), P=0.56]. The median DTDT of VA-ECMO was significantly shorter in survivors [13.0 min (IQR 11.5–18.3) versus 21.0 minutes (IQR 15.5–32.0), P=0.01]. The Kaplan–Meier survival analysis showed that the group with a DTDT ≤20 min had a significantly higher 1-month overall survival rate (P<0.01) and survival rate with a favorable neurological outcome (P=0.01) than that with a DTDT >20 minutes. Using the Cox proportional hazards analysis, DTDT ≤20 minutes and bystander-witnessed significantly affected the overall survival rate at 1 month [adjusted hazard ratio (HR), 0.44; 95% confidence interval (CI), 0.20–0.95; P=0.03 and adjusted HR, 0.31; 95% CI, 0.13–0.74; P<0.01, respectively]. Regarding survival rate with a favorable neurological outcome, the result was relatively similar [adjusted HR, 0.46; 95% CI, 0.22–0.96; P=0.04 and adjusted HR, 0.37; 95% CI, 0.16–0.85; P=0.02, respectively]. Conclusion: This study revealed that the DTDT of VA-ECMO is significantly associated with the 1-month mortality and neurological prognosis of patients with cardiogenic OHCA. However, further studies will be required to confirm these findings. Funding Acknowledgement: Type of funding source: None